A novel green synthesis of CuFe2O4 Nanoparticles from Cissus rotundifolia for photocatalytic and antimicrobial activity evaluation - Jabeen, Sabeeha; Siddiqui, Vasi Uddin; Sharma, Swati; Rai, Smita; Bansal, Pratibha; Bala, Shashi; Raza, Azam; Ahmad, Mohammad Imran; Khan, Abdul Rahman; Khan, Tahmeena (Elsevier, 2024)
This paper reports a novel green fabrication of copper ferrite (CuFe2O4) nanoparticles (NPs) from Cissus rotundifolia plant extract. The NPs were characterized by different spectroscopic techniques.The Fourier transform infrared (FT-IR) spectrum exhibited intrinsic stretching at the tetrahedral position of Fe–O at 591 cm−1 and the octahedral stretching of Cu–O at 402 cm−1 respectively. The fine diffraction pattern in the X-Ray diffraction analysis (XRD) showed the formation of well-crystalline NPs. The mean crystallite size of the NPs was calculated to be 17.33 nm. The High-resolution Transmission Electron Microscopic (TEM) analysis showed roughly spherical shape and irregular morphology of the NPs. The Zeta potential was calculated to be −29.7±0.3 mV, indicating a negative charge over the CuFe2O4 NPs. The formation of spinel ferrite was confirmed from the characterization data. The photocatalytic activity of the CuFe2O4 NPs was examined against the methylene blue (MB) dye, showing 82% degradation under UV–Visible light. The reusability experiment showed that the catalytic activity was not much decreased even till the 4th cycle. The antibacterial activity of the synthesized CuFe2O4 NPs was tested against Bacillus subtilis, Staphylococcus aureus, Bacilus pumilis, Escherichia coli, Pseudomonas aeruginosa, and Salmonella abony through the Agar well diffusion method. A zone of inhibition of 12±0.2, and 11±0.4 mm was obtained against Bacillus subtilis and Bacillus pumilis, whereas against E. coli, P. aeruginosa and S. abony it was found to be 14±0.4, 18±0.3, and 12±0.2 mm respectively at 75 mg/mL dose, showing appreciable antibacterial activity.